Sex-Based Patterns in the Academic Regime at the University of Costa Rica - Alpízar Rojas, Harlen (2026)
Introduction: The study of the conditions and dynamics of promotion for the advancement of female academics has been rendered invisible by the limited access to statistics that can reflect what is happening in this workplace. Considering this, this paper was developed to statistically analyze the situation at the University of Costa Rica, considering the gender of teaching staff. Objective: This study examines the characteristics of teaching staff in the Academic System of the UCR, considering variables reported by the Centre for Academic Evaluation, with special emphasis on regional campuses. Method: Based on secondary analysis of an open institutional database (n = 2067), differences in academic scores, category, academic degree, working hours, and campuses were explored according to the gender of tenured teaching staff. Non-parametric statistical tests and multiple linear regression models were applied. Results: The results show a gap to the detriment of women, especially in regional campuses, where being a woman was associated with an average decrease of 9 points in the academic regime. Although no differences by gender were observed in variables such as academic degree or research experience, there was evidence of lower female representation in the higher categories of the system and limited access to conditions that favour research. Conclusions: It is concluded that the academic evaluation system at the UCR reproduces gender and territorial inequalities, which highlights the need for a review of the system from an intersectional perspective. The findings provide empirical evidence to guide university policies towards greater equity.